Clinical and Laboratory Characteristics of Dengue-Orientia tsutsugamushi co-Infection from a Tertiary Care Center in South India - Basheer, Aneesh (Mediterr J Hematol Infect Dis, 2016)
BACKGROUND: Concurrent infection with multiple pathogens is common in tropics, posing diagnostic and treatment challenges. Although co-infections of dengue, malaria, leptospirosis and typhoid in various combinations have been described, data on dengue and scrub typhus co-infection is distinctly limited. METHODOLOGY: This study was a retrospective analysis of dengue and scrub typhus co-infection diagnosed between January 2010 and July 2014 at a tertiary care center. Clinical and laboratory features of these cases were compared with age and gender-matched patients with isolated dengue fever and isolated scrub typhus. Positive test for dengue non-structural 1 (NS1) antigen was considered diagnostic of dengue whereas scrub typhus was diagnosed by IgM scrub antibodies demonstrated by ELISA. RESULTS: There were 6 cases of dengue-scrub co-infection during the review period which fitted clinical and laboratory profile with a mean age of 42.5 years. Fever, headache, and arthralgia were common. Normal hemoglobin, significant thrombocytopenia, transaminitis, and hypoalbuminemia were identified in these patients. Compared to patients with isolated dengue, those with co-infection had higher pulse rate, lower systolic blood pressure, normal leucocyte counts, higher levels of liver enzymes, greater prolongation of partial thromboplastin time (aPTT) and lower serum albumin. Co-infection was characterized by a lower nadir platelet count compared to scrub typhus, and lesser time to nadir platelet count and longer duration of hospital stay compared to either isolated dengue or scrub typhus. CONCLUSION: Dengue-scrub typhus co-infection may be under-diagnosed in tropics, particularly confounded during dengue epidemics. Normal leukocyte counts, early drop in platelets and hypoalbuminemia in dengue patients could be clues to concurrent scrub typhus infection. Prompt recognition and treatment of scrub typhus in such cases may reduce unnecessary hospital stay and cost.